Soft System Methodology (SSM) Analysis to Increase the Number of Prospective Students - Nikhlis, Neilin; Iriani, Ade; Hartomo, Kristoko Dwi (Universitas Nusantara PGRI Kediri, 2020)
The competition between campus, whether it’s a public college and private college in Central Java, is very tight with the increasing number of interested students for prospective students from various regions. The close competition requires many campuses to compete to provide the best facilities and services. The research objective is expected to support the